Differential Gene Expression and Allele Frequency Changes Favour Adaptation of a Heterogeneous Yeast Population to Nitrogen-Limited Fermentations - Kessi-Pérez, Eduardo I.; Ponce, Belén; Li, Jing; Molinet, Jennifer; Baeza, Camila; Figueroa, David; Bastías, Camila; Gaete, Marco; Liti, Gianni; Díaz-Barrera, Alvaro; Salinas, Francisco; Martínez, Claudio (Frontiers in Microbiology, 2020)
The alcoholic fermentation is fundamentally an adaptation process, where Saccharomyces cerevisiae overcome its competitors and takes over the fermentation process. Despite wine yeast strains seems to be adapted to the stressful conditions of alcoholic fermentation, nitrogen limitations in the grape must causes stuck or sluggish fermentations, generating important economic loses in the wine industry. One way to uncover the genetic bases favouring yeast adaptation to nitrogen deficient environments are selection experiments, where a yeast population undergoes selection under nitrogen-restricted conditions by a certain number of generations, identifying by sequencing, the molecular hallmarks that promotes adaptation. In this work, we performed selection experiments under nitrogen-limited fermentation conditions (SM60), mimicking wine fermentation in bioreactors and using the heterogeneous SGRP-4X yeast population. We sequenced the transcriptome and genome of the population at different time points of the selection process. The transcriptome results showed overexpression in genes coming from the NA (North American/YPS128) strain, a wild non-domesticated isolate. Additionally, the genome sequencing and allele frequency results allowed to map twelve QTLs for the nitrogen-limiting fermentation phenotype. Interestingly, in most of the QTLs mapped, the NA allele frequency increased over the time course of the selection process. Finally, we validated the ECM38 allele from the NA strains as responsible of growth under nitrogen-limited conditions. Altogether, our results showed that wild alleles coming from a non-domesticated isolate (NA) favour the adaptation of a genetically diverse yeast population to nitrogen-limited fermentative conditions, pointing out the potential of these alleles in the genetic improvement of wine yeast strains.